Um estudo sobre o sentido da palavra "coisa": relações semântico-lexicais e referenciação na interpretação textual - Paiva, Fernanda do nascimento (2016)
As a cohesion strategy, words as effective elements of the constitution of a written or spoken text have their meanings changed through specific features of textual construction and they are able to connect the elements that are inside (endophoric) or outside (exophoric) the text through the lexical substitution. In this perspective, the aim of this research is to describe and analyze the use of the word from Portuguese language “coisa”, commonly understood as a generic and vague meaning, showing how this term acquires particular meaning to function as a reference element of cohesion in the oral text. To this end, we used as a corpus eighteen (18) occurrences of the use of "coisa" collected from the corpus "O Linguajar do Sertão Paraibano" observing the process of textual referencing as well as the semantic relationships established in the lexical substitution process. This qualitative, descriptive and interpretive research adopted the theoretical and methodological principles of Lexical Semantics. For the theoretical discussions about the relationship the words have among each other and their textualization, we based our discussion on Antunes (2005, 2012), Henriques (2011), Ilari (2006, 2008), Koch (2004, 2012), Lyons (1981, 1979), Marcuschi (2004, 2008), Oliveira (2008) and Tamba-Mecz (2006). Cavalcante (2003, 2013) and Mondada (2013) served as a theoretical basis as well. The analyses showed that, when establishing exophoric and endophoric references with its textual referent, the word "coisa" builds semantic-lexical relations able to allow its interpretation. Thus, the use of this remitting form, in a given communicative situation, sets aside its character of vagueness and its meaning becomes discursively determined through synonymy, antonymy, hyponymy/ hypernym and meronymy/holonymy relations. Thus, we may say that replacing a noun with proper sense for the generic and vague word "coisa" does not always make its indeterminate information. The swapping of a word that has a special meaning for the word "coisa", which has a maximum generalization, requires an act of interpretation and can be used, for instance, to extend or to restrict some information already introduced or which will be projected in the speech.